Your neighbourhood is not a circle, and you are not its centre. (December 2019) - von Stülpnagel, Rul; Brand, Daniel; Seemann, Ann-Kathrin
Abstract: Neighbourhoods are one of the major areas of focus of place attachment research. However, the understanding of the physical space linked to the term "neighbourhood" is particularly vague. We tested the reliability of one frequently used approach to estimate neighbourhood areas based on a fixed radius centred at each resident's home. Our findings suggest that only few neighbourhoods would be adequately represented by such home-centred circles. We argue that investigations of neighbourhood attachment and interactions require a more sophisticated model of the space people define as their neighbourhood. Highlights: Neighbourhoods have been intensively studied as an object of place attachment. The understanding of the physical "place" of neighbourhoods is particularly vague. Related research fields frequently estimate neighbourhoods by Euclidian buffers. We found few self-defined neighbourhoods are well-represented by a circular buffer. More sophisticated models of the space people define as neighbourhood are required.